2006
DOI: 10.1210/jc.2005-2823
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Bone Mineral Density and Increased Bone Metabolism Rate in Young Adult Patients with 21-Hydroxylase Deficiency

Abstract: Young adult patients with the classical form of CAH have decreased bone density values, compared with healthy controls. This may put them at risk of developing osteoporosis early in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 28 publications
5
65
2
7
Order By: Relevance
“…Osteoporosis risk is increased in CAH patients in adulthood with increasing age when compared to the normal population (6)(7)(8)(9). Therefore, bone health of these patients should be evaluated starting from childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis risk is increased in CAH patients in adulthood with increasing age when compared to the normal population (6)(7)(8)(9). Therefore, bone health of these patients should be evaluated starting from childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic glucocorticoid use has unfavorable effects on bone health through suppression of osteoblastic activity, decreased intestinal calcium absorption, secondary hyperparathyroidism, increased osteoclastic activity, and oversuppression of androgens (4,5). It is known that osteoporosis risk is higher in adult patients with CAH compared to the normal population (6)(7)(8)(9). However, in younger CAH patients there are contradictory results in published studies and case reports that reported that BMD values were not changed or decreased (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported reduced BMD in all PAI patients (2,3), some only in postmenopausal women (4,5) or only in men (6,7), whereas other studies found no significant differences in BMD in either gender (8,9,10). In CAH patients some studies reported no significant differences in BMD between patients with CAH and controls (10,11,12,13,14,15,16), whereas others found reduced BMD in all or some subpopulations of CAH patients (17,18,19,20,21,22,23,24). Until now all studies in this area have had a crosssectional design.…”
Section: Introductionmentioning
confidence: 98%
“…In pregnancies in which the offspring are at high risk for classical 21-OHD, pre-natal treatment with dexamethasone has been reported to be effective in preventing the birth of female babies with ambiguous genitalia [55][56][57]. Although glucocorticoid treatment (sometimes combined with fludrocortisone) continues to be the mainstay of conventional treatment of CAH and has been very helpful and lifesaving in that capacity, its use, even with recent refinements, continues to be plagued with issues regarding over-and under-treatment, growth inhibition, hypertension, obesity, low bone density, testicular adrenal rest tumors, and diabetes [58][59][60]. Our group has been focusing on insulin sensitizing interventions to reduce IR, which is a consistent feature of CAH, as it is with PCOS [61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%